Moderasi Beragama di Desa Kutorojo: Pendekatan Partisipatif dan Regulasi Desa Adat dalam Pengabdian Masyarakat Berbasis Kemitraan Universitas Masyarakat - Kamal, Rahmat; Susanto, Nanang Hasan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This service explores community service in Kutorojo Village to strengthen the richness of religious moderation values. The background is the significant religious diversity in this village. The focus of the service is through participatory approaches and the development of written regulations, by applying Participatory Development Theory and Regulation Theory. The participatory process involved all levels of society, including representatives of various religions, in the drafting of the customary institution regulations. Conclusions demonstrate Kutorojo Village's success in strengthening religious moderation through community empowerment, strengthening customary institutions, and diversity education. Challenges and opportunities are identified, emphasising the need for regulatory strengthening, community empowerment and closer collaboration. The article makes a practical contribution to the literature on community development and religious diversity, demonstrating the implementation of theories and methods in real life. This abstract summarises the essence of the dedication effort with a focus on participatory approaches and written regulations in building religious moderation in Kutorojo Village.